Chlonoidis chilensis (Argentine Tortoise) - Brizio, María Victoria (2021)
ARGENTINA: NEUQUÉN: Departamento Añelo: 25.5 km SE Señal Cerro Bayo YPF oil company base camp, 11 km W Ruta Provincial 8, 8.2 km from E Auca Mahuida Natural Protected Area eastern border, next to a rural booth (37.8203°S, 68.5688°W; WGS 84), 670 m elev. 5 March 2011...